Seismic damage assessment based on structural response and energy approach - Wang, Yi (2008)
A study on seismic damage assessment using response and energy approach is presented in this thesis. A new structural damage assessment model is proposed based on modified force analogy method, and some special features, characteristics and applications of this model are investigated.